Effect of Helicobacter pylori infection on vitamin D levels in old patients with sarcopenia. Issue 2 (24th November 2020) - Bahşi, Remzi; Atmiş, Volkan; Mut Sürmeli, Deniz; Selvi Öztorun, Hande; Turgut, Tuğba; Coşarderelioğlu, Çağlar; Yalçin, Ahmet; Aras, Sevgi; Varli, Murat
Abstract: We aimed to determine the possible relationship between sarcopenia, Helicobacter pylori and 25‐OH vitamin D. A total of 101 patients aged 65 years and over were included in the study, and grouped as sarcopenia (+) and (−) according to the skeletal muscle index (SMI) measured by bioelectrical impedance analysis (BIA). Also, patients were divided into two groups according to the presence and absence of H. pylori infection. There was no significant difference in the frequency of H. pylori infection in patients with and without sarcopenia (37.0% vs 29.7%; P = .485); 25‐OH vitamin D levels were significantly lower (18.25 [6.20‐32.00] μg/L vs 26.30 [9.33‐50.00] μg/L; P < .05) and the frequency of vitamin D deficiency (<20 μg/L) was significantly higher (80.0% vs 29.4%; P < .05) in sarcopenic patients with H. pylori infection than those without H. pylori infection. In addition, H. pylori infection was found to be associated with vitamin D deficiency in patients with sarcopenia (odds ratio: 12.53[1.48‐105.87]; P < .05). Within these findings, we concluded that the presence of H. pylori infection may lead to vitamin D deficiency in patients with sarcopenia.